2004
DOI: 10.1007/s00268-004-7607-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Recurrent Nodular Goiter after Thyroidectomy for Benign Disease: Case‐control Study of 244 Patients

Abstract: Surgery for recurrent nodular goiter is associated with a significant risk of parathyroid and recurrent laryngeal nerve (RLN) morbidity. Total thyroidectomy for benign disease is assessed. The aim of this study was to evaluate the risk factors for recurrence and the morbidity associated with reoperation. From 1969 to 1996 a total of 4334 thyroidectomies were performed, of which 122 were for recurrent nodular goiter (group I: 116 women, 6 men). A matched case-control study of 122 patients operated on for nonrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 16 publications
2
38
6
1
Order By: Relevance
“…surgery has a high incidence of complications such as recurrent laryngeal nerve injury, hypoparathyroidism, and hypothyroidism 3,4,29,30 ; however, the complication rate reported for RFA was low in the study by Baek et al, 25 a 3.3% complication rate with thyroid RFA in their multicenter study. In our current study, the RFA complication rate was found to be lower than that of surgery.…”
Section: Figurementioning
confidence: 66%
See 2 more Smart Citations
“…surgery has a high incidence of complications such as recurrent laryngeal nerve injury, hypoparathyroidism, and hypothyroidism 3,4,29,30 ; however, the complication rate reported for RFA was low in the study by Baek et al, 25 a 3.3% complication rate with thyroid RFA in their multicenter study. In our current study, the RFA complication rate was found to be lower than that of surgery.…”
Section: Figurementioning
confidence: 66%
“…Thus, surgery has been advocated by some clinicians, but after resection of the nodules, patients often have neck scars or hypothyroidism, which seriously affects their quality of life. 3,4 Additional issues include the risks of general anesthesia and postoperative parathyroid function abnormalities. [1][2][3]5 Therefore, minimally invasive alternatives have been explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas thyroid surgery is widely available and safe in many centers, it still carries a 2-10 % risk of complications, such as neck scarring, hypothyroidism, postoperative hypoparathyroidism, recurrent laryngeal nerve injury, and the risks associated with general anesthesia. Surgery is also expensive, and may not be appropriate for a surgically high-risk individual [10,[25][26][27][28][29][30]. Over the last decade, thermal ablation techniques, such as laser ablation (LA), radiofrequency ablation (RFA), high-intensity-focus ultrasound (HIFU), and microwave ablation (MWA), have been proposed for the treatment of benign solid thyroid nodules, with encouraging results.…”
Section: Introductionmentioning
confidence: 99%
“…It was thought to be a safe procedure. Risk of recurrent goiter after subtotal thyroidectomy, which ranges from 3% to 43 % (1)(2)(3) . Suppression of TSH L-thyroxin therapy can be used to prevent the recurrence and is useful only in 30 % of patients (1,(4)(5)(6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%